In vitro antiviral and antimicrobial activities of Spirulina platensis extract - El-Baz, F.K., El-Senousy, W.M., El-Sayed, A.B., Kamel, M.M. (Journal of Applied Pharmaceutical Science, 2013)
Spirulina platensis are filamentous, undifferentiated, non-toxigenic cyanobacteria that have been used as food since ancient times. There have been numerous studies on its antioxidant and antimicrobial actions. In this study antibacterial and antiviral effect of ethanol extract of Spirulina platensis were tested. The reduction of infectious viral units after treatment with ethanol extract of Spirulina platensis was tested. Non toxic doses of Spirulina platensis revealed 53.3%, 66.7%, 76.7%, 56.7%, and 50% reductions in vitro for infectious units of adenovirus type 7, Coxsackievirus B4, astrovirus type 1, rotavirus Wa strain, and adenovirus type 40 respectively. Using disc diffusion method to show the antibacterial effect of ethanol extract of Spirulina platensis against different bacterial strains (Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Enterococcus faecalis) in addition to Candida albicans, inhibition zones were observed with Enterococcus faecalis and Candida albicans.
Keywords: Antiviral, antibacterial, Spirulina platensis, rotavirus, adenovirus, astrovirus.